2017
DOI: 10.1021/acsmedchemlett.7b00310
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure–Activity Relationships of Inhibitors That Target the C-Terminal MEEVD on Heat Shock Protein 90

Abstract: Herein, we describe the synthesis and structure–activity relationships of cyclic peptides designed to target heat shock protein 90 (Hsp90). Generating 19 compounds and evaluating their binding affinity reveals that increasing electrostatic interactions allows the compounds to bind more effectively with Hsp90 compared to the lead structure. Exchanging specific residues for lysine improves binding affinity for Hsp90, indicating some residues are not critical for interacting with the target, whereas others are es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…The data showing that acetyl masking groups can only be removed from serine and tyrosine residues lead to the new design of prodrugs. Starting from two of our most effective compounds, LB51 and LB63, we designed new prodrugs using acetylated serine and tyrosine amino acids (Figure 5(a)) 32 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data showing that acetyl masking groups can only be removed from serine and tyrosine residues lead to the new design of prodrugs. Starting from two of our most effective compounds, LB51 and LB63, we designed new prodrugs using acetylated serine and tyrosine amino acids (Figure 5(a)) 32 .…”
Section: Resultsmentioning
confidence: 99%
“…We had previously reported molecules that targeted heat shock protein 90 (Hsp90), with the lead structures being LB51 and LB63 32 ,33 . However, these active inhibitors had poor cell permeability, and three approaches were used to make these molecules more effective at entering cells: masking groups 10 , d -amino acids 10 , and N -methylation 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Multiple sequence analysis of the ToHSP90β amino acid revealed that it has five conserved signal regions of the HSP90 family with other fish in Figure 2 (Gupta, 1995). The C-terminus of HSP90β has a conserved MEEVD structure that is a feature shared in all the cytosolic Heat shock protein 90 family (Scheufler et al, 2000;Qin et al, 2016;Zhou et al, 2017;Rahimi et al, 2018). Scheufler et al (2000) suggested that MEEVD can be recognized by the TPR domain of HOP (HSP70 and HSP90 organizing protein) and form a molecular chaperone complex with heat shock protein 70.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to evaluating the impact of N‐methylation on LB51 (Figure 10), the McAlpine laboratory also investigated the effect of incorporating d ‐amino acids to generate diastereomers of this lead molecule (Figure 12). [30, 79] Inverting the stereochemistry of asparagine from l to d produced LB51 ‐ d ‐Asn, which had a Caco‐2 cell permeability of 3.9×10 −6 cm s −1 , which was slightly higher than the lead compound's permeability of 3.3×10 −6 cm s −1 . While the cell permeability was similar, incorporating a single d ‐amino acid had a negative impact on the biological activity, where only 25 % inhibition was achieved.…”
Section: Chemical Strategies For Optimizing the Cell Permeability Of mentioning
confidence: 99%